On the Economics of Mandatory Audit Partner Rotation and Tenure: Evidence from PCAOB Data - Gipper, Brandon; Hail, Luzi; Leuz, Christian (The Accounting Review, 2021)
ABSTRACT We analyze the effects of partner tenure and mandatory rotation on audit quality, pricing, and production for a large cross-section of U.S. public firms during 2008–2014. On average, we find no evidence that audit quality declines over the tenure cycle and little support for “fresh-look” benefits provided by the new audit partner. Audit fees decline and audit hours increase after mandatory rotation, but then reverse over the tenure cycle. We also find evidence that audit firms use “shadowing” in preparation for a lead partner turnover. These effects differ by competitiveness of the local audit market, client size, and partner experience. When multiple members of the audit team commence work at a new client, the transition appears to be more disruptive and more likely to exhibit audit quality effects. Our findings point to costly efforts by the audit firms to minimize disruptions and audit failures around mandatory rotations. JEL Classifications: J01; J44; L84; M21; M42.